What if? The economic effects for Germany of a stop of energy imports from Russia - Ruediger Bachmann; David Baqaee; Christian Bayer; Moritz Kuhn; Andreas Löschel; Benjamin Moll; Andreas Peichl; Karen Pittel; Moritz Schularick (CESifo GmbH, 2022)
This article discusses the economic effects of a potential cut-off of the German economy from Russian energy imports. We show that the effects are likely to be substantial but manageable. In the short run, a stop of Russian energy imports would lead to a GDP decline in range between 0.5% and 3% (cf. the GDP decline in 2020 during the pandemic was 4.5%).
Keywords: 330